The Influence of Different Particle Sizes of Roasted Almond Flour on Physical and Sensory Properties - Mohd Nasir, Umie Najwa; Zainal Abidin, Munira; Zulhilmi Cheng, Mohamad Zulhafiz Shafiq (Enhanced Knowledge in Sciences and Technology, 2025)
This study focuses on the development of reduced-gluten muffins using almond flour examine the effects of different particle sizes of roasted almond flour (18, 30, and 60 mesh) on their physical and sensory properties and to address the growing demand for gluten-reduced bakery products due to health concerns such as gluten intolerance, celiac disease, and dietary preferences for low-gluten foods. A control formula using 100% wheat flour was included for comparison. The objective was to assess the influence of almond flour particle size on attributes such as height, weight loss, moisture con-tent, texture, colour, and overall sensory acceptance. The muffins were evaluated using standard laboratory techniques, including texture analysis, moisture determination, and sensory evaluation using a 9-point hedonic scale. The results revealed that smaller almond flour particle sizes improved the structural integrity and sensory characteristics of the muffins. Formula 3 (60 mesh almond flour) exhibited the greatest height (5.2 cm ± 0.1), highest springiness (0.88 ± 0.02), and superior sensory acceptability (overall liking score of 7.8 ± 0.3), comparable to traditional wheat-based muffins (8.0 ± 0.2). Conversely, Formula 1 (18 mesh almond flour) demonstrated lower height (4.5 cm ± 0.1), higher firmness (12.6 N ± 0.4), and reduced consumer preference (overall liking score of 6.2 ± 0.4). Statistical analysis (ANOVA, p < 0.05) confirmed significant differences in these attributes among the formulas. The findings highlight that finer almond flour enhances water absorption, gas retention, and overall batter uniformity, resulting in improved baking and sensory outcomes. This study provides valuable insights for the food industry, particularly for manufacturers developing gluten-reduced bakery products that cater to health-conscious consumers. The results support the use of optimized almond flour particle sizes to achieve desirable texture and sensory characteristics, potentially increasing consumer acceptance in commercial gluten-free or reduced-gluten markets.